Brazilian Smart Cities Through the Lens of Information Technology: A Systematic Mapping Study - Boniati, Bruno B.; Frantz, Rafael Z. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248306, 2026)
Research Context: The densification of urban populations has posed significant challenges to the scientific community, public administrators, and the private sector, demanding innovative and sustainable solutions to enhance the quality of life in these environments. Smart cities utilise information technology resources to harness data, applications, and devices, thereby enabling intelligent and integrated services across diverse urban contexts. Scientific and/or Practical Problem: Despite extensive research work across various application domains, there is a lack of recent and comprehensive studies that systematically examine the application of information technology within the Brazilian smart city research community. Proposed Solution and/or Analysis: This paper aims to map and categorise studies conducted by Brazilian authors that explore the use of information technology to deliver solutions in smart city scenarios, based on the indicator dimensions defined by the ABNT NBR ISO 37122 standard. Related IS Theory: The study is grounded in General Systems Theory, as the categorisation of primary studies facilitates a broader and more structured understanding of this research domain. Research Method: A systematic mapping of the literature was undertaken using the ACM Digital Library, IEEE Xplore, ScienceDirect, Scopus, and Web of Science databases, encompassing papers published between 2014 and 2024. Summary of Results: From a total of 1,041 unique publications identified during the search phase, 642 were selected and categorised. The findings reveal the thematic and contextual concentration of studies, the temporal evolution of publications by type, the national institutions and researchers with the greatest influence, as well as the principal venues for disseminating research outcomes. Contributions and Impact to IS area: This work offers a comprehensive and up-to-date synthesis of smart city approaches from the standpoint of information technology, contributing to the advancement of knowledge within the Brazilian research landscape.